A model to predict the oscillation frequency for drops pinned on a vertical planar surface. (10th December 2021) - Sakakeeny, J.; Deshpande, C.; Deb, S.; Alvarado, J.L.; Ling, Y.
Abstract: Abstract : Accurate prediction of the natural frequency for the lateral oscillation of a liquid drop pinned on a vertical planar surface is important to many drop applications. The natural oscillation frequency, normalized by the capillary frequency, is mainly a function of the equilibrium contact angle and the Bond number ( $Bo$ ), when the contact lines remain pinned. Parametric numerical and experimental studies have been performed to establish a comprehensive understanding of the oscillation dynamics. An inviscid model has been developed to predict the oscillation frequency for wide ranges of $Bo$ and the contact angle. The model reveals the scaling relation between the normalized frequency and $Bo$, which is validated by the numerical simulation results. For a given equilibrium contact angle, the lateral oscillation frequency decreases with $Bo$, implying that resonance frequencies will be magnified if the drop oscillations occur in a reduced gravity environment.